Peran Mediasi Kredibilitas Influencer Pada Pengaruh Aktivitas Pemasaran Media Sosial Terhadap Pembelian Online Impulsif - Zalfaa Azzahra Fadhlila; Asmai Ishak (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research aims to identify impulse buying behavior, source credibility, and the marketing influence of Tasya Farasya influencers on Instagram. The population used was 17-40 years old. The total sample is 323 respondents who are active Instagram users and follow the Tasya Farasya account. Research data was obtained using a questionnaire via Google Forms. The data analysis technique uses Structural Equation Model (SEM) on AMOS 24 software. As a result, influencer credibility mediates the relationship between perceived social media marketing activities and online impulse purchases through attractiveness, expertise, and trust. Social media marketing activities have a positive effect on the source credibility dimension. Only attractiveness and trust prove a positive influence on online impulse buying. Influencer expertise has not been proven to influence impulse buying behavior.